A two genes – for – one gene interaction between Leptosphaeria maculans and Brassica napus. Issue 1 (5th April 2019) - Petit‐Houdenot, Yohann; Degrave, Alexandre; Meyer, Michel; Blaise, Françoise; Ollivier, Bénédicte; Marais, Claire‐Line; Jauneau, Alain; Audran, Corinne; Rivas, Susana; Veneault‐Fourrey, Claire; Brun, Hortense; Rouxel, Thierry; et al.
Summary: Interactions between Leptosphaeria maculans, causal agent of stem canker of oilseed rape, and its Brassica hosts are models of choice to explore the multiplicity of 'gene‐for‐gene' complementarities and how they diversified to increased complexity in the course of plant–pathogen co‐evolution. Here, we support this postulate by investigating the AvrLm10 avirulence that induces a resistance response when recognized by the Brassica nigra resistance gene Rlm10 . Using genome‐assisted map‐based cloning, we identified and cloned two AvrLm10 candidates as two genes in opposite transcriptional orientation located in a subtelomeric repeat‐rich region of the genome. The AvrLm10 genes encode small secreted proteins and show expression profiles in planta similar to those of all L. maculans avirulence genes identified so far. Complementation and silencing assays indicated that both genes are necessary to trigger Rlm10 resistance. Three assays for protein–protein interactions showed that the two AvrLm10 proteins interact physically in vitro and in planta . Some avirulence genes are recognized by two distinct resistance genes and some avirulence genes hide the recognition specificities of another. Our L. maculans model illustrates an additional case where two genes located in opposite transcriptional orientation are necessary to induce resistance. Interestingly, orthologues exist for both L. maculans genes in other phytopathogenic species, with a similar genome organization, which may point to an important conserved effector function linked to heterodimerization of the two proteins.